2014
DOI: 10.1111/jace.12997
|View full text |Cite
|
Sign up to set email alerts
|

CuInSe2 Formation from CuSe/In2Se3 and Cu2Se/In2Se3 Powders: Reaction Kinetics and Mechanisms

Abstract: CuInSe2 (CIS) powders were synthesized using CuSe, Cu2Se, and In2Se3 as the raw materials. The formation mechanisms and reaction kinetics from CuSe/In2Se3 and Cu2Se/In2Se3 powders in a selenium atmosphere were investigated. It was observed that the formation temperature of α‐CIS powders synthesized using Cu2Se/In2Se3 as the raw materials was higher than that using CuSe/In2Se3. Both reactions for Cu2Se/In2Se3 and CuSe/In2Se3 mixtures follow one‐dimensional diffusion‐controlled reactions with apparent activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The black powder obtained from the reaction of copper, antimony and selenium precursors in 1 h showed formation of only Cu 2‐x Se instead of CSSe. Careful analysis of the XRD pattern confirmed formation of hexagonal phase of Cu 2‐x Se NCs owing to three strong to medium intensity peaks at 2θ 27.6°, 45.6° and 54.2° . This further underlines the importance of the reaction parameters such as time and temperature.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The black powder obtained from the reaction of copper, antimony and selenium precursors in 1 h showed formation of only Cu 2‐x Se instead of CSSe. Careful analysis of the XRD pattern confirmed formation of hexagonal phase of Cu 2‐x Se NCs owing to three strong to medium intensity peaks at 2θ 27.6°, 45.6° and 54.2° . This further underlines the importance of the reaction parameters such as time and temperature.…”
Section: Resultsmentioning
confidence: 71%
“…It is interesting to consider the same reaction by employing different capping agent i. e. oleyl amine. Indeed, when the reaction was performed with desired ratios at 220 °C for just 30 min., UV‐Visible spectrum of the reaction mixture revealed absorption relevant to the product however, XRD analysis of dried product showed presence of mixture of Cu 2‐x Se and CuSbSe 2 NCs [Figure (IV 30 min)]. Finally, 1hr reaction time at the same temperature was enough to get phase pure CuSbSe 2 NCs (JCPDS 01–075‐0992).…”
Section: Resultsmentioning
confidence: 99%
“…Combined with previous studies by other researchers [11,[19][20][21][22][23], it can be suggested that the reactions be carried out as follows:…”
Section: Elementmentioning
confidence: 97%
“…As is known, nanoparticles with fine and uniform size are the key issue in fabricating targets with high-density and homogeneous composition. The solvothermal method and heat injection method were used to obtain CIGS nanoparticles [10][11][12]. However, there exist some problems, such as the separation of the CuInSe 2 (CIS) phase and the CuGaSe 2 (CGS) phase, the composition deviation of the raw powders from the obtained particles, and the low production efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Cu(In,Ga)Se 2 (CIGS) materials are regarded as the suitable chalcopyrite absorbers for the applications in various thin‐film based solar cells. Till date, the conversion efficiencies of CIGS‐based solar cells exceeding 20% have been demonstrated . However, elevation of the grain sizes of CIGS films and the reduction in defects in absorber layers are crucial for the fabrication of CIGS‐based devices with high conversion efficiency .…”
Section: Introductionmentioning
confidence: 99%